Merancang sistem keamanan berbasis face recognition pada layanan sirkulasi perpustakaan - Murdani, Hati; Bella, Elsa Listia; Fatwanto, Agung (Daluang: Journal of Library and Information Science, 2024)
Purpose. This article aims to design a security system for library circulation services based on facial recognition, focusing specifically on collection lending services. The proposed system seeks to usher libraries into a new era where efficiency and security are prioritized, while also serving as an example of innovation in modern library circulation security systems.Methodology. The system design follows an object-oriented approach, employing the UML language with activity diagrams and use case diagrams to model the processes.Results and discussion. The proposed system includes a use case diagram that outlines system activities and the relationships between actors and the system, as well as an activity diagram that details the structured flow of the book borrowing process, integrating facial recognition technology.Conclusions. Facial recognition is proposed as a means to enhance the security of library book borrowing processes by providing automatic, dual-layer identity verification. By implementing facial recognition in the circulation service security system, libraries are expected to prevent unauthorized access and misuse while improving service efficiency.